2008
DOI: 10.1128/aac.01083-07
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Antibiotic Resistance during Therapy for Infections Caused by Enterobacteriaceae Producing AmpC β-Lactamase: Implications for Antibiotic Use

Abstract: Enterobacter spp., Serratia marcescens, Citrobacter freundii, and Morganella morganii are characterized by chromosomally encoded AmpC ␤-lactamases and possess the ability to develop resistance upon exposure to broad-spectrum cephalosporins. To determine the incidences of the emergence of resistance during antimicrobial therapy for infections caused by these organisms and the effect of the emergence of resistance on patient outcomes, all patients who were admitted to the Asan Medical Center (Seoul, Republic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 12 publications
(17 reference statements)
6
105
3
4
Order By: Relevance
“…also found that 19% of patients receiving broad-spectrum cephalosporins developed resistant Enterobacter isolates and that resistance was more likely to appear if the original isolate came from blood (156). A recent study evaluated 732 patients with infections due to Enterobacter spp., S. marcescens, C. freundii, or M. morganii (57). Resistance emerged in 11 of 218 patients (5%) treated with broad-spectrum cephalosporins, more often in Enterobacter spp.…”
Section: Clinical Relevance Chromosomal Ampc Enzymesmentioning
confidence: 99%
“…also found that 19% of patients receiving broad-spectrum cephalosporins developed resistant Enterobacter isolates and that resistance was more likely to appear if the original isolate came from blood (156). A recent study evaluated 732 patients with infections due to Enterobacter spp., S. marcescens, C. freundii, or M. morganii (57). Resistance emerged in 11 of 218 patients (5%) treated with broad-spectrum cephalosporins, more often in Enterobacter spp.…”
Section: Clinical Relevance Chromosomal Ampc Enzymesmentioning
confidence: 99%
“…is a major concern since it appears among ca. 10% to 20% of patients treated with broad-spectrum cephalosporins (35)(36)(37). Also, once selected, AmpC overproduction is stable, and approximately 30% to 40% of ECC isolates are currently resistant to third-generation cephalosporins worldwide (38,39).…”
mentioning
confidence: 99%
“…Increased incidence of nosocomial infections and broad resistance to third generation cephalosporins, penicillins and quinolones are a serious problem. However, fourth generation antimicrobials remain effective for treatment but with serious side effects [29]. Aminoglycosides, quinolones, trimethoprim/sulphamethoxazole, and carbapenems displayed good activity against Gram-negative pathogens including Enterobacter species [30].…”
Section: Assessment Of Antimicrobial Susceptibilitymentioning
confidence: 99%